Local Respiratory Viral Surveillance Can Focus Public Health Interventions to Decrease Influenza Disease Burden. (25th January 2021) - Crouch, Elena; Gonzalez, Jonathan; Jacobs, Erin; Schaecher, Kurt; Kehl, Margaret; Ottolini, Martin; Malloy, Allison
ABSTRACT: Background: Respiratory viruses are an important cause of nonbattle injury disease and contribute to the top seven reasons for medical encounters. In the absence of vaccines that provide complete protection against these viruses, viral surveillance can identify disease burden and target virus-specific preventative measures. Influenza infection, in particular, has significant adverse effects on force readiness. Methods: We tracked the frequency of 16 respiratory viruses at Walter Reed National Military Medical Center tested for during routine patient care using multiplex polymerase chain reaction and rapid antigen testing. We collected data on the date and location of the testing, as well as the age of the individual tested from two consecutive respiratory viral seasons. Results: During the first year of data compilation (2017-2018), 2556 tests were performed; 342 (13.4%) were positive for influenza A and 119 (4.7%) were positive for influenza B. After influenza, the most common families of viruses identified were rhino/enterovirus (490 [19.2%]). During the second year (2018-2019), 4, 458 tests were run; 564 (12.7%) were positive for influenza A and 35 (0.79%) were positive for influenza B, while rhino/enterovirus was identified in 690 (15.4%). Influenza peaked early during the 2017-2018 season and later during the 2018-2019 season. Importantly, during the 2017-2018 season, the vaccine was less effective for the H3N2 strain circulating that year and viral surveillance quickly identified a hospital-specific outbreak and a larger disease burden. This was in contrast to the 2018-2019 vaccine which exhibited higher effectiveness for circulating strains. Conclusion: Our data highlight the seasonality of respiratory viruses with a focus on influenza. By tracking respiratory viruses in Department of Defense communities, we may be able to predict when influenza may cause the greatest burden for distinct organizational regions and prescribe with greater precision preventative protocols by location, as well as rapidly determine vaccine efficacy. Our current data suggest that when vaccine strains are mismatched, rapid upfront targeting of antivirals may be warranted, but when the vaccine strains are better matched, late season peaks of disease may indicate waning immunity and should be monitored.